Mechanistic investigation of the nickel-catalyzed carbonylation of alcohols - Sabater, Sara; Menche, Maximilian; Ghosh, Tamal; Krieg, Saskia; Rück, Katharina S. L.; Paciello, Rocco; Schäfer, Ansgar; Comba, Peter; Hashmi, A. Stephen K.; Schaub, Thomas (Organometallics, 2020)
The carbonylation of alcohols represents a straightforward and atom-efficient methodology for the preparation of carboxylic acids. It is desirable to perform these reactions under precious metal-free and low-pressure conditions, with regioselectivity control. In this work, we present a detailed mechanistic study of a catalytic system based on NiI2, which can carbonylate benzylic alcohols in a highly regioselective manner to the corresponding branched carboxylic acids, core motifs for nonsteroidal drugs.
Gesehen am 02.09.2020